Produksi Xilitol Menggunakan Hidrolisat Tongkol Jagung (Zea mays) Oleh Meyerozyma caribbica InaCC Y67 - Faradila Ayu, Near Putri; Nurhayati, N; Thontowi, Ahmad; Kusdiyantini, Endang; Kanti, Atit; Hermiati, Euis (Bioma : Berkala Ilmiah Biologi, 2021)
Xylitol (C5H12O5) is a non-carcinogenic polyalcoholic sugar. Xylitol is beneficial for diabetics because it can be metabolized without insulin. Corn cobs contain 30% xylose which can be fermented into xylitol by microorganisms. Xylitol can be produced by fermentation of xylose and few microorganisms. Meyerozyma caribbica is a yeast that has been proven to produce xylitol and inhibitorâ€™s resistant. The aim of this research is to test the xylitol productivity by Meyerozyma caribbica InaCC Y67 using corn cobs hydrolyzate and the effect of the volume of fermentation media on xylitol productivity by Meyerozyma caribbica InaCC Y67. The method was carried out by culturing Meyerozyma caribbica InaCC Y67 as a starter on YPD media.Â  Fermentation using 100 mL Erlenmeyer with the variation of fermentation volume is 10 ml and 75 ml, agitation 175 rpm and 30 oC. Parameters were measured based on the dry weight of cells, xylose and xylitol. Data were analyzed using fermentation kinetics. The results of analysis showed that the higher xylitol production was found in the fermentation volume 75 ml with an efficiency value of 7,171%. The highest xylitol production was at the 48th hour with production value of 2.050 g/L. Results from research shows that Meyerozyma caribbica InaCC Y67 can produce xylitol with corn cobs hydrolyzate. The right volume of fermentation in the fermentation process can also increase the productivity of xylitol.